Working paper- Literature review on Potential options for livestock feed improvement in Malawi - Chikwanha, Obert; Chiduwa, Mazvita S.; Malunga, Innocent; Chimonyo, Vimbayi G.P.; Mhlanga, Blessing; Nyagumbo, Isaiah; Thierfelder, Christian (International Maize and Wheat Improvement Center, 2024)
Smallholder farmers in Malawi are confronted with many challenges, encompassing both biophysical and socioeconomic aspects, which negatively impact their livelihoods. Unfortunately, these challenges are often addressed in fragmented approaches, lacking a holistic perspective, that prioritises isolated components and dimensions of their livelihoods. Instead of prioritising the improvement of nutrient content in forages and grains, crucial for both quantity and quality of protein, interventions tend to overlook this aspect. Consequently, food security remains compromised, exacerbating issues related to hidden hunger. This study was designed to explore opportunities in the contrasting communities within the Mangochi district, characterised by aridity, with the higher potential (semi-arid) sites of Kasungu where CIMMYT implements activities under Mixed Farming Systems initiatives. The study assessed various forage options within the framework of sustainable intensification aimed at enhancing livelihoods across diverse landscapes in Malawi, highlighting opportunities for maximising synergistic benefits and minimising potential trade-offs. The first activity was a comprehensive literature review, delineating the array of feed/ forage resources available for smallholder farmers. The review further evaluated the challenges and opportunities inherent in their pursuit of optimal animal productivity. In Malawi, smallholder farmers benefit from a rich assortment of feed resources for their livestock, primarily relying on local sources such as natural rangeland pastures, which serve as the primary source of their feed inventory. The main challenge of rangeland pastures is the decline in biomass and quality, particularly in the dry season. Although a minority, predominantly dairy farmers, leverage improved forages like Napier and Rhodes grass through the cut-and-carry system, the prevalence of such practices remains limited. Following harvest, cereal and legume crop residues emerge as crucial supplementary feeds during this period. The dominant crop residues are maize stover and bran, and groundnut haulms. Regrettably, there’s a notable oversight regarding alternative sources of energy- and protein-rich feeds, such as small cereal grains, cassava, legumes (including fodder trees/ shrubs and herbaceous forages), insect-based meals, and hydroponic fodder. Notably, fodder derived from ligneous trees and shrubs presents a promising solution to address feed shortages during the dry season, boasting high protein content, a critical nutrient deficit during this period. Commercial feeds and supplements are prevalent among large-scale livestock farmers, as the adoption among smallholders is constrained primarily by prohibitive costs. The second activity was to identify the potential sources of feed improvement for livestock aligned to the different agroecological regions. Key informant interviews (KII) were carried out in Kasungu (n = 26) and Mangochi (n = 11), complemened by six focused group discussions (FGDs), with three conducted in each district. Additionally, chemical profiles of forages were analysed in both districts, with 11 samples from each. The KII showed that maize-based farming is the dominant agricultural practice in the surveyed districts, followed by crop-livestock mixed farming. Livestock breed preferences varied between districts; however, local breeds were prevalent in both districts. Across the two districts, 57% of the respondents in Kasungu reported that farmers use supplements, whilst in Mangochi, it was 43%. Maize bran (100%) and stover (92%) were reported as the main energy supplements, with groundnut the dominant protein supplement in both districts, reported by close to two-thirds of the KIIs. During the FGDs, farmers highlighted numerous obstacles, including challenges with agricultural inputs (i.e., seeds and fertiliser), worsened by climate change impacts such as delayed rainfall onset and increased pest and disease prevlence. In addition to diseases and pest prevalence, feed shortages during the dry season were a major factor influencing the reduction in animal production. Despite feed and diseases being primary limitations to animal production among smallholder farmers, it was the financial constraints that wield the greatest influence as farmers could not afford supplementary feed or the cost of purchasing veterinary medicines. Despite these challenges, there’s optimism about adopting Sustainable Intensification practices, as farmers acknowledge its potential to enhance productivity and optimise resource utilisation even after the project phases out, reflecting hope for increased yields and household incomes. Leucaena leucocephala had the greatest crude protein content (35.3%) across the two districts. Snot apple tree (Azanza garckeana) leaves and Bambusa balcooa were second and third in terms of CP content in Kasungu after L. leucocephala at 23.2% and 22.2%, respectively. In Mangochi, the greatestCP content was in the order of Moringa oleifera (25%), Khaya nyasica (22.1%) and cassava (Manihot esculenta) leaves (21.4%). Based on the relative feed value, snot apple leaves and giant milkweed (Calotropis procera) ranked the highest in Kasungu and Mangochi at 112 and 108, respectively. The third objective was to propose options for impact pathways for crop-livestockbased poverty escape for the Kasungu and Mangochi districts. Despite the myriad of challenges in achieving the goals of SI-MFS, adopting the practices can yield benefits such as increased productivity, enhanced resilience, and improved livelihoods for rural farmers. In land-limited areas like Mangochi, introducing non-conventional crops can boost productivity and address food insecurity, while integrating small stock rearing with crop production could potentially optimise land use and reduce reliance on external inputs. Smallholder farmers in both districts can sustainably manage their livestock feed resources through innovative strategies like utilising tree/ shrub and herbaceous legume foliage for both nutritious feed and enhanced soil fertility. Supporting smallholder farmers to use local resources for feed, coupled with training in livestock management, particularly, feed formulation (e.g., Pearson square method) could enhance the feed quality and improve animal nutrition and production. Preservation of feed resources (e.g. haymaking) and proper preparation techniques (i.e., chopping or grinding crop residues) to improve feed intake, digestibility and animal productivity is recommended. To improve the adoption of some of these technologies, capacity building for achieving change needs to occur throughout the continuum from youth through inservice learning for professionals in research, extension, and other private and public sectors, as well as institutional capacity building. Successful implementation of these technologies will require a revitalised and efficient extension service, including commnity-based agents and farmer-to-farmer programs, which are crucial in disseminating knowledge and facilitating the adoption of sustainable practices. In addition, integrated marketing and value-addition initiative programs can also enhance market access and farmer incomes, contributing to a holistic approach to addressing the complex challenges faced by smallholder farmers in these communities.